PATE AND THE TRANSFORMATION OF SOUTHERN CULTURE - Bamrungpanit, Sukrittawat; Jittra, Arisara; Chayprateep, Wasana; Yosboon, Warocha; Sriplod, Sirichai; Loungpanang, Jaturong; Taengwong, Yuttana; Dangpeng, Dechawat; Aupatumnarakorn, Bubpachart; Suwanrot, Thamasan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The purpose of this study is to discuss Pate and the transformation of Southern culture. The researcher proposes to present the history and Pate pattern of the southern product’s identity. Pate is the traditional garment of the South, which is the local wisdom that shows the way of life from past to present. In addition to using Pate as a garment, at present, it has been developed and used for different purposes, such as ceremonies, customs, or social status clothing. Pate is a beautiful art that can be created in the form of a product to add value to the people in the community or a group of manufacturers that can have their own identity. In product model development, the focus is mostly on handmade. It is a valuable Pate product that reflects the bond between people and fabric. The use of Pate cloth in fresh colors and beautiful patterns is a medium for the use of creativity in art and design, which is veiled with various beliefs related to Pate. Delicacy combined with perseverance also presents the importance of Pate to the way of life of the Southern people and the changes in the current social context.